Application of mastopexy technique using Klein’s solution. A 40 cases experience. - Heriberto Chávez Sánchez; Liliana Espinosa Chang; Dagmaris Losa Pérez (Medisur)
Background: Breasts has always played an important role in female image. Breast ptosis is a disease which is frequently consulted to plastic surgeons. A correction was performed applying mastopexy in a minor outpatient surgery using modified Klein´s solution in minimal concentrations of lidocaine which avoid bleeding. Objectives: To describe the aesthetic results in the usage of mastopexy with Klein´s solution specifying: behavior of pain, bleeding during the surgery process, presence of complications and the satisfaction exploration in surgical operated patients. Method: A series of cases consisted of 40 patients who came to the plastic surgery consultation at the University Hospital “Dr. Gustavo Aldereguía Lima” in Cienfuegos city with breast ptosis from January 2005 to January 2006, using three mastopexy techniques (pedicle fixation, periareolar fixation, and dermal fixation). Pain was assessed during the operation and after the operation, as well as the satisfaction level of the patients and the aesthetic results obtained. Results: 75 per cent of the studied patients were among 20 and 39 years old. Klein´s solution modified with an anesthetic method was administered. 87.5 per cent stated no not feel pain showing the efficacy of the solution. Complications were minimal, only in two of the patients who presented partial wound dehiscence without any other surgical intervention. Conclusions: It was evidenced the efficacy of the Klein´s solution in the breast ptosis correction. It is recommended the usage of this solution due to the advantages it offers. It is also very economic in its usage.